Unusual neck masses encountered in remote areas of Sikkim - Kesari, Santosh Prasad; Chakraborty, Priyanko; Anand, Aseem; Mukherjee, Subhasish (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Neck masses are one of the most common presentations in the ENT practice and they are a challenge in the diagnosis and management. The masses may be of congenital, inflammatory, or neoplastic origin. An accurate clinical assessment conducted while taking into account pertinent anatomical and developmental viewpoints, accompanied by well-planned investigative parameters, may aid in making an early diagnosis. Our is a series of three cases where in which we have described the finding of all the three cases in detail, first case is of 70 years female with right sided neck swelling which ultimately turned out to be right venous aneurysm. Second being a case of a young kid misdiagnosed as other infections and treated for long time, which ultimately responded with ATT. Lastly, a young kid presenting with multinodular goitre. We need to be ready for surprise and be ready to deal with unusual cases with different management options.